MITIGATING COGNITIVE CHALLENGES FACED BY TEACHERS OF ENGLISH IN TEACHING AND LEARNING READING IN NIGERIAN SECONDARY SCHOOLS: Received: 06th November 2023; Revised: 02nd January 2024, 7th January 2024; Accepted: 1st December 2023 - Idowu, Olufemi Stephen; Raphael , Ogundeko, Ibukun (PUPIL: International Journal of Teaching, Education and Learning, 2024)
Teachers, especially teachers of English language face considerable challenges when teaching reading at the various school levels. Reading is the act or process of receiving and interpreting information in language via the medium of print. This paper identifies some of the challenges encountered by English teachers while instructing and facilitating the teaching and learning reading among secondary schools generally special focus on Nigeria. It highlights the multifaceted nature of the challenges, encompassing area such as diverse student intellectual abilities, insufficient cognitive engagement, language barriers. This paper review various studies on reading and in Nigerian schools, identify recurrent problems and the gaps relating to cognitive challenges. It explores potential solutions to mitigate these flaws, emphasizing the pivotal importance of tailored instructional strategies and tooling, collaborative approaches between parents/guardian and managements of school, and the integration of active technological apparatus to the system. The paper recommended that, regular workshops with a cognitive approach should be organized for all teachers of English to enable them handle reading effectively, this training will create a drive-in teacher to ensure that students under their tutelage are fluent readers. More so, in- service training should also be an integral part of continuing teacher education and teachers should be supported in order to increase their level of confidence when teaching reading.